Interpretations of Tafsir Scholars on Toxic Behavior in Family Life in the Modern Era - Zahra Dwiyanti, Rahma; Fauzan Adim; Althaf Husein Muzakky (JOURNAL OF QUR'AN AND HADITH STUDIES, 2025)
This study examines toxic behavior within modern families through Qur’anic interpretation. Integrating classical and contemporary tafsir with real-time social-media evidence offers the first multidisciplinary framework for diagnosing and remedying toxicity in Muslim households—an angle seldom addressed in previous scholarship. Toxic behaviors such as verbal abuse, emotional neglect, one-sided dominance, and psychological manipulation have become increasingly complex in the digital era due to social, economic, and cultural pressures. A descriptive qualitative approach was employed through library research, analyzing Qur’anic verses, tafsir literature, and relevant social media content. Findings show that such behaviors deviate from Quranic values emphasizing justice, compassion, and healthy communication. Scholars like Quraish Shihab and As-Suyuthi highlight mutual consultation, fairness, and spirituality in conflict resolution. Foundational concepts of sakinah, mawaddah, and rahmah emerge as practical guidelines for harmonious, toxicity-free relationships, urging Muslim families to reinvigorate these values.